Immunomodulatory and Acute Toxicity Studies of Peronema canescens Jack Leaves: in vivo Hematological Analysis and in vitro IL-6 Gene Expression Inhibition - Muhammad Ryan Radix Rahardhian; Fahriza Ardiansyah; Yasmiwar Susilawati; Gofarana Wilar; Sri Adi Sumiwi; Jutti Levita; Muchtaridi Muchtaridi (The Indonesian Biomedical Journal, 2025)
BACKGROUND: Peronema canescens Jack is traditionally employed in the treatment of inflammation, malaria, and immune-related disorders. Despite its traditional use, scientific evidence on its immunomodulatory effects, interleukin (IL)-6 modulation, hematological impact, as well as its related acute toxicity data remains limited. Therefore, this study was conducted to investigate the immunostimulatory potential of P. canescens leaf extract through in vitro and in vivo assessments and evaluate its acute toxicity profile.METHODS: The in vitro immunomodulatory activity of P. canescens ethanolic extract, n-hexane fraction (NHF), ethyl acetate fraction (EAF), and water fraction (WF) were assessed by measuring IL-6 inhibition in lipopolysaccharide-stimulated RAW 264.7 macrophages. For in vivo analysis, Balb/C mice were divided into six groups: a normal control (Na-CMC), a positive control (50 mg/kg BW/day Stimuno Phyllanthus niruri extract), a negative control (80 mg/kg BW/day cyclophosphamide as immunosuppressant), and 3 treatment groups receiving P. canescens extract at doses of 100, 200, and 400 mg/kg BW/day. Hematological parameters, including white blood cell (WBC) counts, lymphocyte percentages, and neutrophil percentages, were analyzed. Acute toxicity studies were performed by administering P. canescens extract at doses of 300, 2000, and 5000 mg/kg BW over observation period.RESULTS: EAF exhibited the most pronounced IL-6 inhibition in vitro. In vivo, the administration of P. canescens extract at 200 and 400 mg/kg BW significantly elevated WBC and lymphocyte levels while concurrently reducing neutrophil counts. No mortality or neurotoxic manifestations were observed, confirming the P. canescens extract’s safety profile up to 5000 mg/kg BW.CONCLUSION: P. canescens leaf extract, particularly EAF, demonstrates robust immunomodulatory activity with a favorable safety margin. These findings underscore its potential therapeutic application in immune modulation.KEYWORDS: Peronema canescens Jack, immunomodulatory, IL-6 inhibition, acute toxicity, hematology, cytokines